Penciptaan Motif Batik Tulis Abstrak Gradasi dari Ragam Garis - Regreat Suasmiati (Jurnal Pendidikan dan Penciptaan Seni, 2022)
The art of batik culture in particular has existed since ancient times, and until now batik has developed and is a work of national culture. Batik is one of the cultural arts that is special, namely a combination of art and technology, is a work of art that combines the art of motifs or decoration and color art which is processed through dyeing, dabbing and shaving (Sewan, 1982). This study aims to show that Variety of Lines can generate new ideas in the presentation of batik motifs. The emergence of new patterns according to local cultural wisdom is unique in strengthening the nation's identity as a world cultural heritage. Seeing the good prospects of the development of the art of batik, it is necessary to pay attention to basic things such as quality, basic materials (fabric, dyes, etc.), the workmanship system and the development of ideas in its presentation so as to provide economic value and have a long-term positive impact on the art of batik itself. Variety of Lines can be used as an idea to bring up new motifs. The results of this study indicate that the Variety of Lines can generate new ideas in the presentation of batik motifs and also helps to flex the use of canting in the written batik technique.